Mackerel Shrimp Sausages High in Protein, Iron, Zinc and Calcium for Stunted Toddlers - Endang Sri Wahyuni; Nawasari Indah Putri Sejati (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Stunting in children is associated with motor problems and death, stunted brain development, motor, mental growth, and reduced physical capacity, productivity and economy. The incidence of stunting in Indonesia is still higher than the maximum stunting incident set by WHO. Nutrition-based interventions can reduce the incidence of stunting. Local food-based foods that children like can be an alternative to increase the intake of protein and micronutrients needed in children's growth. This study aimed to determine the most preferred formula of rebon flour substitution in mackerel sausage. The research design was experimental with a completely randomized design method. The product consists of F0, F1, F2, F3, F4, and F5. Formulation F0 was a control sausage formulation made from mackerel: rebon flour with a ratio of 100%:0%. F1 was the formula for mackerel rebon sausage with the composition of mackerel: rebon flour (95%:5%), F2 (90%:10%), F3 (85%:15%), F4 (80%:20%) and F5 (75%:25%). The ANOVA test showed that the panelists' preference for each formulation differed significantly (p=0,000). The greater the percentage of rebon flour subsites used in mackerel sausage, the less favorable the aroma, color, taste, and texture. Friedman's test showed that mackerel sausage substituted with 5% dry rebon flour was the most preferred sausage formulation. 100 g of boiled sausage contained 147 kcal of energy, 11,72 g of protein, 20,67 g of carbohydrates, 18 mg of Fe, 3,69 mg of Zn and 217,73 mg of calcium. The energy content of sausages can be increased by serving sausages after frying.